Comparación histoquímica de albura y duramen de tres especies de Quercus - Rivera Nava, Laura; Quintanar Isaías, Alejandra; de la Paz Pérez Olvera, Carmen (Instituto de Ecología, A.C., 2016)
Histochemical and some quantitative features of sapwood and heartwood cells of Quercus glabrescens, Q. potosina y Q. eduardii are described. The trees were collected in different sites of Huayacocotla, in Veracruz State. The results show that sapwood of the species are very similar in histochemical and quantitative trends but heartwood differ on chemical deposits of gelatinous fibers, and violet deposits of polisacharids present on rays and also the petrification processes in Q. potosina rays. Cell wall quality and the relationship between dimensions and types of chemical compounds are discussed as well.